IntelCity, comprehensive management platform for smart cities - Poncela-González, Javier; Pérez, N.; Moreno, J.M.; Memon, M. (My University, 2014)
Modern cities contain a wealth of information that is usually scattered among a myriad of organisms. For citizens it is many times difficult and confusing to access this information. Cities must find a way to put all this information at the disposal not only of the citizens but any employee that takes part in the operation and maintenance of the city. One of the problems that appear is that each city department has organized its information independently of others, thus leading to an heterogeneous ecosystem of databases and platforms. This paper describes a solution to access all the information available in a city through a mobile platform. A customizable user application for the Android operating system is described. The solution can be deployed in any city as the application dynamically obtains the information from remote servers that hold access to the databases.
Keywords: Sistemas de telecomunicaciones; Smart City